2017
DOI: 10.2495/cmem-v6-n5-910-920
|View full text |Cite
|
Sign up to set email alerts
|

Impact of spatial variability of earthquake ground motion on seismic response of a railway bridge

Abstract: This paper studies the impact of spatially varying ground motions on the responses of a railway bridge. The evaluation of the seismic hazard for a given site is to estimate the seismic ground motion at the surface. This is the result of the combination of the action of the seismic source, which generates seismic waves, the propagation of these waves between the source and the site, and the local conditions of the site. Firstly, the seismic ground motions are modelled by assuming the base rock motions of the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The results of these works indicate that neglecting local site effect can lead to underestimate seismic excitation for a multi-scale structure [2,[7][8][9][10][11]. Most of these studies have proposed methods of generating seismic signals taking into account spatial varying ground motion [9,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these works indicate that neglecting local site effect can lead to underestimate seismic excitation for a multi-scale structure [2,[7][8][9][10][11]. Most of these studies have proposed methods of generating seismic signals taking into account spatial varying ground motion [9,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies on the influence of local site conditions on seismic response of multi-scale structures have shown that neglecting this factor gives rise to an undervaluation of seismic demand [2,7,10,11,23].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the amplification effect of seismic waves can be very significant in the case of sites composed of sedimentary deposits [17]. This phenomenon of the local site effect has encouraged several researchers to undertake studies on the influence of this effect on the estimation of seismic ground motions [2,12,13,[18][19][20][21]. Further research has addressed the assessment of the impact of the local site effect on dynamic response of extended structures [11,22,23].…”
Section: Introductionmentioning
confidence: 99%